A PRELIMINARY EXPERIMENTAL STUDY ON THE COMPARISON OF CONCRETE STRENGTH TESTS AND BOHME ABRASION TEST FOR BASALT AGGREGATE CONCRETE - Tugrul, Esra (My University, 2025)
It is very important to determine whether the strength of concrete structures, especially under the effect of earthquakes, is sufficient to prevent loss of property and life. In this context; the tests required for the concrete to be used in the structure should determine the most suitable concrete properties for the intended use of the structures. With the present study, by utilizing basalt aggregate in concrete production, both concrete strengths will be increased and economic contribution will be provided since its reserves are abundant. In addition to the concrete compressive strength and concrete splitting tensile strength tests performed on structural concrete for the building of earthquake-resistant structures, alternative strength tests should also be tested to determine the mechanical properties of concrete with the developments in concrete production and application technologies. One of them is the Bohme abrasion strength test, which is performed to determine the resistance to abrasion. In the present study, concrete compressive strength, concrete splitting tensile strength, and Bohme abrasion strength tests were performed experimentally for a series of conventional concrete specimens produced using basalt aggregate. Relatively high concrete strength values were obtained for the tested concrete specimens. It was observed that the concrete compressive strength value and concrete splitting tensile strength value increased in direct proportion to each other, while the Bohme abrasion loss value decreased with a high determination coefficient. Thus, it indicates that the concrete strength increases with decreasing Bohme abrasion loss value.
Keywords: Compressive strength; Splitting tensile strength; Earthquake; Basalt aggregate; Bohme abrasion strength